HUBUNGAN LAMA KERJA DAN STATUS PELATIHAN PROGREMER TB DENGAN ERROR RATE PROGRAM TUBERCULOSIS PARU DI KABUPATEN KOLAKA UTARA - Dwiana, Ester; rufi, Ma’; Zamli, Zamli (Ensiklopedia of Journal, 2024)
Abstract: Tuberculosis (TB) is one of the 10 highest causes of death worldwide and the main cause of death from infectious agents. Tuberculosis (TB) is still a big problem in Indonesia, currently Indonesia ranks 2nd with the highest TB burden in the world. The aim of this research is to see the relationship between length of work and training status of TB programmers with the error rate of the pulmonary TB program in North Kolaka Regency. This type of research was an observational cross sectional study in North Kolaka Regency involving 30 TB programmers spread across 16 Community Health Centers in North Kolaka Regency. This research instrument uses a questionnaire and observation sheet. Analysis uses univariate and bivariate analysis with (chi-square test). The results of this study show that the results of the chi-square test show that the significant value for the probability of length of work is sig-p (0.016) = < α-value = 0.05 and training status is sig-p (0.215) > α-value = 0, 05. This proves that there is a relationship between length of work and the Error Rate of the Pulmonary TB Program in North Kolaka Regency, while training status has no relationship with the Error Rate of the Pulmonary TB Program in North Kolaka Regency.Keywords: Error Rate, Length of Work, Training Status